PERSEPSI MAHASISWA AKUNTANSI BERDASARKAN GENDER TERHADAP ETIKA BISNIS DAN ETIKA PROFESI (STUDI KASUS : PTS DAN PTN DI KOTA BANJARMASIN) - Ruslinda Agustina; Ni Nyoman Suarniki; Suyanti - (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,This study aims to provide empirical evidence of whether there is a difference in perception by gender on the ethics of business and professional ethics in private and state accounting students in the city of Banjarmasin. The sampling technique used was quota sampling random sampling. The number of samples in this study were 282 respondents. Determination of the number of samples using a statistical test version of the 16 Formula Slovin.The results of this study indicate that there are differences in the perception of business ethics based on gender private and state in Banjarmasin city it is based on the results of Kruskal Wallis test different perceptions about business ethics derived significant value of 0.000 <0.05. Then in the perception of the ethics of the profession there are different perceptions about the professional ethics of gender-based private and state in Banjarmasin city it constituted the Kruskal Wallis test results differing perceptions about the ethics of the profession was obtained significant value of 0.966> 0.05.The conclusion of this study was the difference in the perception of gender-based accounting students of business ethics, and there was no difference in the perception of accounting students by gender on the ethics of the profession. Limitations of this research was the respondents sampled only among accounting students. So suggestions for future research in order to add another variable, expanding the research object with respondents not only among students but can accounting of public accountants and accountants among educators.